Solving Schrödinger equation for two dimensional potentials using supersymmetry - Drigo Filho, Elso (Eclética Química, 1997)
The formalism of supersymmetric Quantum Mechanics can be extended to arbitrary dimensions. We introduce this formalism and explore its utility to solve the Schrödinger equation for a bidimensinal potential. This potential can be applied in several systems in physical and chemistry context , for instance, it can be used to study benzene molecule.